Chemogenetic Modulation of Orexin Neurons Reverses Changes in Anxiety and Locomotor Activity in the A53T Mouse Model of Parkinson’s Disease - Stanojlovic, Milos; Pallais, Jean Pierre; Kotz, Catherine M. (Frontiers in Neuroscience, 2019)
Parkinson’s disease (PD) is the second most common neurodegenerative disease. PD symptomology is recognized as heterogeneous and in addition to motor function decline, includes cognitive, mood, sleep and metabolic disorders. Previous studies showed early reductions in anxiety and locomotion in the A53T mice model of PD. Since inflammation and astrogliosis are an integral part of PD pathology and impair proper neuronal function, we were keen to investigate if behavioral changes in A53T mice are accompanied by increased inflammation and astrogliosis in the Hippocampus (Hipp) and motor cortex (mCtx), brain regions involved in the regulation of anxiety and locomotion, respectively. To test this, we used 3, 5, and 7-month old A53T mice to examine anxiety-like behavior, locomotion, and expression of inflammation and astrogliosis markers in the hippocampus (Hipp) and motor cortex (mCtx). Further, we examined the presence of alpha-synuclein accumulation in orexin neurons and orexin neuronal loss. The data show early reductions in anxiety like behavior as well as increased locomotor activity, which was accompanied by inflammation and astrogliosis in the Hipp and mCtx. Due to the persistence of the orexin neuron population in A53T mice and the involvement of orexin in anxiety and locomotor regulation, we hypothesized that chemogenetic modulation of orexin neurons would reverse the observed reductions in anxiety-like behavior and the increases in locomotor activity in these animals. We showed that chemogenetic activation of orexin neurons in A53T mice restores anxiety-like behavior back to control levels without affecting locomotor activity, whereas the inhibition of orexin neurons reverses the elevated locomotor activity without any effects on anxiety-like behavior. This study exemplifies the complex role of orexin neurons in this model of PD and demonstrates the novel finding that changes in locomotor and anxiety-like behavior are accompanied by inflammation and astrogliosis. Together, these data suggest that the orexin system may play a significant role in early and late stages of PD.